2012
DOI: 10.1002/pd.3885
|View full text |Cite
|
Sign up to set email alerts
|

Origin of trisomy: no evidence to support the ovarian mosaicism theory

Abstract: This study found no evidence of fetal ovarian mosaicism for trisomies 16, 21 and 22.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…More recently, Robles and colleagues examined seven euploid fetuses and identified trisomy 21 in 1/425 (0.2%) leptotene cells but in none of 985 zygotene or pachytene cells [Robles et al, ]. Finally, in the only study conducted after that of Hultén and colleagues [Hulten et al, ], Morris and colleagues analyzed both fetal ovarian and skin samples, and observed extremely low levels of trisomy 21 mosaicism in each of the two tissue types (2/8,365 = 0.02% in ovarian cells and 5/8,245 = 0.06% in skin cells) [Morris et al, ]. Thus, taken together, the results of four different analyses suggest that—for reasons that are unclear—the original report of Hulten et al [] markedly overestimated the incidence of trisomy 21 in fetal oocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Robles and colleagues examined seven euploid fetuses and identified trisomy 21 in 1/425 (0.2%) leptotene cells but in none of 985 zygotene or pachytene cells [Robles et al, ]. Finally, in the only study conducted after that of Hultén and colleagues [Hulten et al, ], Morris and colleagues analyzed both fetal ovarian and skin samples, and observed extremely low levels of trisomy 21 mosaicism in each of the two tissue types (2/8,365 = 0.02% in ovarian cells and 5/8,245 = 0.06% in skin cells) [Morris et al, ]. Thus, taken together, the results of four different analyses suggest that—for reasons that are unclear—the original report of Hulten et al [] markedly overestimated the incidence of trisomy 21 in fetal oocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, only one subsequent study has attempted to repeat the study. In an analysis of eight samples and 51,146 cells, Morris and colleagues were unable to replicate the original observations [Morris et al, ]. However, neither the original study nor the study of Morris and colleagues analyzed different stages of meiotic prophase, and Hulten et al [] did not analyze chromosomes other than 21.…”
Section: Introductionmentioning
confidence: 97%
“…Morris et al [2012] essentially repeated the work of Hultén's group but with the use of alternative probes. In the second study, preliminary work was first carried out on fetal ovarian tissue from fetuses diagnosed with trisomy 21 to determine the optimal meiotic stage for detecting trisomic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some question the Oocyte Mosaicism Selection model. In 2012, Morris et al found no evidence of fetal oocyte mosaicism for trisomies 16, 21 and 22. They analyzed eight karyotypically normal female fetuses between 10 and 14 gestational weeks; they used FISH to find the possibly trisomic cells in ovarian tissues without differentiating the meiotic and pre‐meiotic cells with immune reactions, and used skin samples from all fetuses for karyotyping and control.…”
Section: Discussionmentioning
confidence: 99%